A study of verbal-visual learning preferences and multimedia learning in higher learning institutions - Liew, Tze Wei; Tan, Su-Mae; Mahmud, Yuzi; Salam, Sazilah (2010)
This paper describes how visual and verbal learning styles can be accommodated in multimedia learning environment. We investigated the effects and possible aptitude treatment interactions between verbal-visual learning styles and multimedia presentation strategy in higher learning institution. A multimedia courseware on C Programming was designed to allow two modes of presentation based on verbal-visual learning preferences – verbal presentation consists of text and audio while the visual presentation consists of text and animation. Students of Diploma in Business and Diploma in Business Information Systems at Multimedia University were randomly assigned to visual and verbal presentation mode and given a learning test to measure their learning achievement.Participants also took the Index of Learning Style Questionnaire to determine their visual/verbal scores. A one-way ANOVA was administered to investigate potential aptitude treatment interaction (ATI) between verbal-visual learning preferences, multimedia presentations and learning scores.Results from the experiment provided no support for significant ATI. Further exploratory analysis however, showed significant relationship between academic major differences (Business and Business Information Systems) and verbal-visual learning preferences. Results also suggested that scaffolding effects improve learners’ performance within the multimedia learning environment.